IMPACT OF TOTAL ISCHEMIC TIME ON THE RECOVERY OF REGIONAL WALL MOTION ABNORMALITY AFTER STEMI IN PATIENTS UNDERGOING PCI - SHINWARI, MI; KHAN , FU; KHAN, AA; AMIN, S; ALI, MA; SIDDIQE, U (Biological and Clinical Sciences Research Journal, 2023)
This study was designed to evaluate the impact of total ischemic time (TIT) on the recovery of regional wall motion abnormality (RWMA) in patients undergoing percutaneous coronary intervention (PCI) after ST-elevation myocardial infarction (STEMI). This was a single-center retrospective study of 155 patients with STEMI who underwent PCI at the Medical Teaching Institute-Hayatabad Medical Complex in Peshawar from May 3, 2022, to October 5, 2022. The primary outcome was the recovery of RWMA, as assessed by the wall motion score index (WMSI) at discharge. Longer TIT was associated with a decreased likelihood of recovery of RWMA (adjusted odds ratio [OR], 0.72; 95% confidence interval [CI], 0.59-0.89; P=0.002). Patients with TITs of 180 minutes or less were more likely to experience a decrease in WMSI (OR, 3.02; 95% CI, 1.36-6.71; P=0.007) if they were older, had an anterior myocardial infarction, and had higher baseline WMSI. Our study demonstrates that longer TIT is associated with a reduced likelihood of recovery of RWMA after STEMI in patients undergoing PCI. Timely reperfusion is crucial for improving myocardial function and optimizing clinical outcomes in these patients. Strategies to minimize TITs, such as pre-hospital activation of the catheterization laboratory, streamlined processes for door-to-balloon time, and advanced imaging techniques to guide revascularization, may improve outcomes in this patient population.